2017
DOI: 10.1111/jpn.12765
|View full text |Cite
|
Sign up to set email alerts
|

Influence of l‐carnitine and l‐arginine on protein synthesis and maturation of the semitendinosus muscle of lightweight piglets

Abstract: SummaryLightweight (LW) piglets from large litters display impaired growth performance compared with heavier littermates. This study investigated the growth performance and muscle development of early-weaned LW piglets (birthweight <1.2 kg) from large litters (17.3 ± 3.0 total born per litter), fed ad libitum a milk replacer supplemented with either l-carnitine (CAR) or l-arginine (ARG) from day 7 to day 28 of age. In total, 36 female and entire male Swiss Large White piglets, weaned on day 7 of age, were arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…In another study of the same group with an identical experimental design but a slightly lower L‐carnitine dose (400 mg/piglet and day), L‐carnitine supplementation also failed to significantly improve growth performance, semitendinosus muscle weight and myofibre size of low birth‐weight piglets ( n = 30, female and castrated from Swiss Large White sows) reared with a mainly cow milk product‐based milk replacer from day 7 to 28 of age (Madsen, Mueller et al., ). It is likely that the same reason as in the study before (Madsen, Seoni et al., ) accounts for the lack of effect of supplemental L‐carnitine.…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 52%
See 2 more Smart Citations
“…In another study of the same group with an identical experimental design but a slightly lower L‐carnitine dose (400 mg/piglet and day), L‐carnitine supplementation also failed to significantly improve growth performance, semitendinosus muscle weight and myofibre size of low birth‐weight piglets ( n = 30, female and castrated from Swiss Large White sows) reared with a mainly cow milk product‐based milk replacer from day 7 to 28 of age (Madsen, Mueller et al., ). It is likely that the same reason as in the study before (Madsen, Seoni et al., ) accounts for the lack of effect of supplemental L‐carnitine.…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 52%
“…Nevertheless, the results of this study indicated that the beneficial effect of early‐postnatal L‐carnitine supplementation in low birth‐weight piglets on myofibre number at weaning disappears during the post‐weaning/growing and finishing period. Also, no effect of L‐carnitine supplementation on BW gains and gain‐to‐feed ratio was observed in a very recent study with light‐weight piglets (birth weight <1.2 kg, n = 36, female and entire male from Swiss Large White sows), which were early weaned on day 7 of age and artificially reared with a milk replacer based on cow milk products and offered either 0 (control) or 480 mg L‐carnitine per day until day 28 of age (Madsen, Seoni, Kreuzer, Silacci, & Bee, ). In addition, this study did not find any effects of supplemental L‐carnitine on skeletal muscle weights and contractile and metabolic traits of skeletal muscle of early‐weaned pigs (Madsen, Seoni et al., ).…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 99%
See 1 more Smart Citation
“…This is evidenced by the up-regulated expression of selected genes in the STM l of these piglets at birth. An increased expression of MyHC IIb and of MyHC IIx indicates increased muscle maturation, owing to a shift towards a more glycolytic and less oxidative metabolism in the muscle (46) . Primary fibres start to express slow MyHC and mature into type I slow muscle fibres, whereas secondary fibres express fast MyHC and mature into type IIx or IIb fibres (47) .…”
Section: Discussionmentioning
confidence: 99%
“…The delayed growth of LBW piglets is mainly due to a slower development of skeletal muscle as the myogenic activity is usually impaired in these animals during the fetal and early postnatal period 3 , 4 . These disadvantages could cause long-term negative effects in LBW piglets 1 and different adapted feeding strategies have been developed to compensate the growth delay and improve the body composition of LBW piglets 5 7 . Feeding with amino acids can stimulate protein synthesis in all tissues, especially in skeletal muscle as reviewed by Davis et al 3 .…”
Section: Introductionmentioning
confidence: 99%